Antônio José da Silva e o labirinto da mística judaica : religiosidade e resistência na literatura cristã-nova no inicio do século XVIII - Fonseca, Josevânia Souza de Jesus (2014)
The work that the reader now has in hand corresponds to a story about the Sephardic culture that spread after the Atlantic Diaspora in the 15th century. He was drafted from the yarn left by Antônio José da Silva, nicknamed "the Jew", in four of his operas, Vida de D. Quixote de La Mancha, Esopaida, ou Vida de Esopo, Os Encantos de Medéia e Anfitrião, ou Júpiter, e Alcmena, presented between 1733 and 1736 at the Teatro do Bairro Alto in Lisbon. The operas are in tune comedies that bring, between the lines, marks the time when the French lived, as well as the previous temporalities stays, mixed to established models of literature and mythology. Through them, the author suggests his dissatisfaction with society in which was inserted, by means of the criticism of the Inquisition, to justice, to customs and, especially, to religion, leaving evidence of cryptic religiosity subtext practiced by Jewish cabalists. The objective of this work is to analyze the escamoteados cabalistic aspects in these texts, because we understand that they are constituent part of the worldview of the new Christians judaizers. To this end, resorted to the categories of analysis of the Cultural history, making use of changes in scales of observation, indicting and method of comparison of elements present in the texts with the more general aspects of law and Jewish mysticism. The research reveals that, in addition to the primary intention of the comedies of the Jew, to laugh at the Lisbon society through satire of customs and institutions, there is a message of resistance directed to new Christians judaizers. The research is structured in three chapters: Antônio José da Silva: um Cavaleiro Andante na Lisboa do Século XVIII; A Religião da Cavalaria Andante; e Os Recônditos Arcanos da Cavalaria Andante. In the first chapter, we sought to relate the character Don Quixote to the figure of the knights errant Kabbalists, as well as introduce customs and references to Jewish mystical elements present in the Opera Vida de D. Quixote de La Mancha, the first comedy of the harvest of the Jew. The second chapter reflects on the Religion of the Cavalry Andante in allusion to the "law of Moses", as she was known the cryptic form practiced religiosity by new Christians, constantly identified in inquisitorial documents and, consequently, in the literature of centuries of prohibition of Jewish worship. Finally, Os Recônditos Arcanos da Cavalaria Andante which made an interpretation of evidence identified in the operas in the light of Jewish mysticism, still little explored aspect of Sephardic culture.